vHIT Testing of Vertical Semicircular Canals With Goggles Yield Different Results Depending on Which Canal Plane Being Tested - Wittmeyer Cedervall, Louise; Magnusson, Måns; Karlberg, Mikael; Fransson, Per-Anders; Nyström, Anastasia; Tjernström, Fredrik (Frontiers in Neurology, 2021)
Objective: The use of goggles to assess vertical semicircular canal function has become standard method in vestibular testing, both in clinic and in research, but there are different methods and apparatus in use. The aim of this study was to determine what is the cause of the systematic differences between gain values in testing of the vertical semicircular canals with two different vHIT equipment in subjects with normal vestibular function. Study design: Retrospective analysis of gain values on patients with clinically deemed normal vestibular function (absence of a corrective eye-saccade), tested with either Interacoustic’s or Otometric’s system. Prospective testing of subjects with normal vestibular function with the camera recording eye-movements of both eyes. Finally, 3D-sensors were placed on different positions on the goggles measuring the actual vertical movement in the different semicircular planes. Results: In the clinical cohorts the gain depended on which side and semicircular canal that was tested (p<0.001). In the prospective design the combination between stimulated side and semicircular canal and position of the recording device (right/left eye) highly influenced the derived gain (p<0.001). The different parts of the goggles also moved differently in vertical direction during vertical semicircular canal testing. Conclusion: The gain values when testing function of the vertical semicircular canals seem to depend upon which eye is recorded and which semicircular plane is tested and suggests caution when interpreting and comparing results when different systems are used both clinically as well as in research. The results also imply that further research and development is needed to obtain accurate vertical semicircular canal testing, in regard to both methodology and equipment design.